THE ISSUES OF LEGAL REGULATION OF RATIONAL ENVIRONMENTAL MANAGEMENT ON AGRICULTURAL, FORESTRY AND WATER FUND LANDS - VLADIMIROV Igor Aleksandrovich; MULLAGALEEV Ilnur Afruzovich (Правовое государство: теория и практика)
The relevance of the study is due to the need to improve the legal regulation of the modern process of involvement in the civil turnover of agricultural land, recreational coastal zones and forestry fund, which are the place of attraction for potential agrarian business entities. If an effective legal mechanism for the rational management of such lands is established, the state will be able to solve the problem of sustainable development of rural territories, as stated in the National Security Strategy of the Russian Federation. According to the Strategy, the national interests in the sphere of agricultural management and development for the long-term period are: sustainable development of agriculture and rural areas, restoration and increase of efficiency of agricultural land use, prevention of reduction of its area. The article analyses agrarian, land and natural resources legislation in terms of the effectiveness of law enforcement practices on agricultural lands, coastal recreation zones and the forest fund. The purpose of the study is to identify the legal specifics of establishing the legal regime of rational environmental management on agricultural, forest and water fund lands. The following methods are used in the preparation of the article: empirical methods of comparison and description; theoretical methods of formal logic; the specific scientific method of interpretation of legal norms. Results: the article concludes on the need for state strategic planning of land resources management, including agricultural land, and the development of environmental management in rural areas; that the state needs to remove existing administrative and legislative barriers that limit the efficiency of environmental management on agricultural, forest fund, and recreational water fund lands. The article also concludes that the national spatial data system being created may be used, among other things, for the purpose of promptly establishing and changing the types of permitted use of land plots in case it is impossible to use them for effective business activities carried out on agricultural, forest and w ater fund lands.